Pengaruh Celebrity Endorser, Customer Review, dan Harga Terhadap Minat Pembelian Produk Scarlett Whitening di E-Commerce (Lembaga Pengembangan Kinerja Dosen, 2026)
This research investigates how celebrity endorsements, customer reviews, and pricing affect consumers’ intention to purchase Scarlett Whitening products. Amid intense competition in the skincare industry, firms are required to focus not only on product features but also on psychological and perceptual aspects that influence consumer behavior. Celebrity endorsers contribute to strengthening brand trust, customer reviews offer insight based on user experiences, while price reflects consumers’ perceived value of the product. This study adopts a quantitative explanatory design, with data obtained from 204 respondents through structured questionnaires using a five-point Likert scale. The collected data were analyzed using multiple linear regression with SPSS version 26. The findings indicate that celebrity endorsers, customer reviews, and price have both simultaneous and individual positive and significant impacts on purchase intention. An adjusted R-square value of 0.274 suggests that these variables account for 27.4% of the variation in consumers’ purchase intention. Overall, the results highlight that appropriate endorsements, trustworthy reviews, and competitive pricing collectively enhance consumers’ intention to purchase Scarlett Whitening products